Secrets of recording : professional tips, tools & techniques - Bregitzer, Lorne (Mastering music., 2009)
Packed with studio tips and professional tricks and more than 200 illustrations, Secrets of Recording by Lorne Bregitzer makes it easier than ever to create pro-quality music at home. This book is the only reference you will ever need to start producing and engineering your music, or other artists' music, in your own home studio. Covering less than ideal acoustics, solving problems before they occur, tools of the editing phase, and much more, you can gain the knowledge and know-how to make your recordings sound like pro recordings -- understand the technology, use it in the right way and you can make a good recording great. . Reveals the "engineering secrets" used by the top producers, exposes the hidden skills of music production . Make good sound great, by understanding the technology, using it properly and applying professional techniques . For the home studio setup, be creative & resourceful and achieve great results- without professional resources!